Clinical results of autologous fat transfer for basal thumb arthritis with a minimum of three years’ follow-up - Elisabeth M. Haas-Lützenberger; Iana Emelianova; Moritz C. Bader; Sinan Mert; Nicholas Moellhoff; Wolfram Demmer; Ursula Berger; Riccardo Giunta (Bone & Joint Open)
Aims: In the treatment of basal thumb osteoarthritis (OA), intra-articular autologous fat transplantation has become of great interest within recent years as a minimally invasive and effective alternative to surgical intervention with regard to pain reduction. This study aims to assess its long-term effectiveness. Methods: Patients diagnosed with stage one to three OA received a single intra-articular autologous fat transplantation. Fat tissue was harvested from the abdomen and injected into the trapeziometacarpal (TMC) joint under radiological guidance, followed by one week of immobilization. Patients with a minimum three-year post-procedure period were assessed for pain level (numerical rating scale), quality of life (Mental Health Quotient (MHQ)), the abbreviated version of the Disabilities of Arm, Shoulder and Hand questionnaire (QuickDASH)), and grip and pinch strength, as well as their overall impression of the treatment. Wilcoxon tests compared data from pre-intervention, and at one and three years post-intervention. Results: Out of 136 treated joints, the study involved 87 patients (37 patients were loss to follow-up, and 12 patients (9%) who underwent resection arthroplasty) with a median follow-up of 4.9 years (IQR 5.4 to 5.9). Pain, both at rest and during stress, significantly improved at one year and remained stable through three years. Sex, age, and stage of disease were not associated with postoperative pain levels. Patient-reported outcome measures for QuickDASH and MHQ improved up to at least three years post-treatment. Patients reported high satisfaction and willingness to recommend the procedure. Grip and pinch strength did not significantly change over time. Conclusion: The data show that autologous fat transfer has a longer-lasting effect in two-thirds of re-examined patients. If patients had an initial positive response, the pain-reducing effect lasted for at least three years. Therefore, this minimally invasive approach can offer a valuable treatment alternative for basal thumb OA.